Documentation of sample sizes and panel attrition in the German Socio Economic Panel (SOEP) (1984 until 2012) - Martin Kroh (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
[Introduction] This data documentation is meant to provide SOEP users with a general overview of the longitudinal development of the survey over the past 29 years and the derivation of weights that compensate for selective panel attrition. In the first section, we report the number of household and personal interviews by cross-section. We do so for the entire SOEP sample as a whole, as well as for sub-samples A through K individually. The SOEP study surveys not only the original sample from the first wave, but also households and persons that entered the survey at later points in time. They enter, for example, when SOEP households split (i.e., individuals move out and form their own households), when people move into SOEP households, and when an original sample member gives birth to a new sample member. For a detailed review of the SOEP inclusion rules for new sample units and their treatment within the weighting framework see Spiess et al. (2008) and Schonlau et al. (2011). The second section of the present paper on the longitudinal development of the SOEP reports descriptive figures of the participatory behavior of the original sample members and the entrance patterns of new sample members. Households may leave the survey for several reasons. SOEPs weighting strategy distinguishes between survey-related reasons and reasons unrelated to the survey (for a detailed description of the SOEP weighting strategy, see Rendtel 1995 and Schonlau et al. 2013 and for a general overview, Haisken-DeNew & Frick 2001). We ignore panel attrition of the latter form due to respondents moving abroad or dying, since these cases technically represent an exit from the underlying population. The second section of this paper provides initial evidence on the risk of survey-related panel attrition in different groups of the original sample units (e.g., in different subsamples, age, educational, and income groups). The third section reports in more detail on the occurrence of unsuccessful follow-ups to household addresses by cross-section and sub-sample, and sub-sample-specific regression models of the probability of unsuccessful follow-ups in 2012 based on the characteristics of households measured in 2011. The fourth section does the same for the second form of survey-related attrition: refusals. Based on the regression models of unsuccessful-follow ups and refusals, we derive predicted observation probabilities. The inverse of the product of these predicted probabilities gives the longitudinal weighting variables for the year 2012: BCHBLEIB and BCPBLEIB. Based on the inverse of the probability of observing households and persons in 2011, the staying probability in 2012, and additional post-stratification to meet benchmarks of known marginals of the underlying population in 2012, we derive the cross-sectional weights BCHHRF and BCPHRF. The final section of this paper documents some summary statistics of the development of the longitudinal and the cross-sectional weights by sub-sample and wave.
Keywords: 330